2003
DOI: 10.1097/01.ccm.0000079609.81180.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of standardized orders and provider education on head-of-bed positioning in mechanically ventilated patients

Abstract: Standardizing the process of care via the addition of an order specifying head-of-bed position significantly increased the number of patients who were placed in the semirecumbent position. In an era of cost-conscious medicine, interventions that utilize protocols and education programs should be emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 22 publications
2
35
1
1
Order By: Relevance
“…Previous research [13][14][15][16][17][18][27][28][29] demonstrated the difficulty with obtaining an HOB elevation of 30º to 45º. This study demonstrated that patients can maintain an HOB elevation of at least 30º.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Previous research [13][14][15][16][17][18][27][28][29] demonstrated the difficulty with obtaining an HOB elevation of 30º to 45º. This study demonstrated that patients can maintain an HOB elevation of at least 30º.…”
Section: Discussionmentioning
confidence: 73%
“…In a survey, 27 ICU nurses identified the probability of the patient sliding down in the bed as the primary concern with HOB at 45º. In the current study, only 1 patient had problems with sliding at 45º.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence of a unit policy recommending semirecumbency did not affect backrest elevation. Various studies [33][34][35] have shown that implementation of unit protocols and objective measurement devices can result in improved compliance with semirecumbency. We did not directly assess nurses' awareness of unit protocols or use of measurement devices available to them in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Helman et al 32 suggests that nurses may be inclined to place patients in lower HOB positions at night to facilitate sleep. However, our findings do not support time of day as a predictor of HOB elevation.…”
Section: Time Of Daymentioning
confidence: 99%